2016
DOI: 10.1016/j.amsu.2016.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Case report of an anal adenocarcinoma arising from a perineal lump

Abstract: Anal adenocarcinoma is a rare condition and can arise in chronic inflammatory states such as in Crohn's disease, or in a chronic fistula-in-ano. We report our diagnosis and management of a patient who presented with a large perineal lump with a long-standing history of perianal fistulous disease. This was initially evaluated with a Magnetic Resonance Imaging, and the diagnosis was confirmed with biopsy. Multimodality treatment with chemoradiotherapy and surgery should be offered to achieve the best outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…It seems that radiotherapy and surgery provide the best 5-year disease-free survival rates, reaching 54%[15]. Primary CRT should be combined with APR; otherwise, it may be associated with high rates of local recurrence and distant metastases [1]. Contemporary studies of small sample sizes have suggested chemoradiotherapy mandated before abdominoperineal resection to achieve R0 resections and negative margins, with complete response rates as high as 85% (6/7)[16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It seems that radiotherapy and surgery provide the best 5-year disease-free survival rates, reaching 54%[15]. Primary CRT should be combined with APR; otherwise, it may be associated with high rates of local recurrence and distant metastases [1]. Contemporary studies of small sample sizes have suggested chemoradiotherapy mandated before abdominoperineal resection to achieve R0 resections and negative margins, with complete response rates as high as 85% (6/7)[16].…”
Section: Discussionmentioning
confidence: 99%
“…After neoadjuvant therapy, positive circumferential resection margins achieved during abdominoperineal resection were present in only 8% of patients[18]. The current literature suggests that when the disease is potentially curative, radical surgery with either pre- or postsurgery chemoradiotherapy should be attempted to achieve the best overall survival[1]. However, in a retrospective analysis of 22 patients, the conclusions demonstrated that local and regional control with radiation with or without chemotherapy resulted in high relapse rates in AA[3], and it is suggested that the use of radiation therapy among patients with AA did not appear to significantly influence survival rates[6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a survey conducted by Abel et al, 12 most clinicians only occasionally encounter patients with anal adenocarcinoma. Therefore, the majority of recent descriptive studies are clinical case reports, 1315 and there is a lack of sufficient information to generate guidelines for uniform treatment recommendations. 16,17 Moreover, molecular perturbations that might serve as targets for therapy are completely unknown.…”
Section: Introductionmentioning
confidence: 99%